SELF-STUDY AS A MEANS OF FORMING LEGAL COMPETENCE OF FUTURE SPECIALISTS OF CIVIL PROTECTION - Rotar, V. (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
The peculiarities of self-study of future specialists of civil protection in a higher educational establishment are revealed. It is proved that legal competence of specialists of civil protection is the basic feature of professional activitiy. The purpose of the article is to analyze the role of self-study of future specialists of civil protection in the process of formation of their legal competence. Methods: method of theoretical synthesis for defining the notions of "self-study", "legal competence"; method of system-structural analysis, implementation of which helped to single out the basic principles for organization of self-study of cadets. It is determined that it is necessary to implement the appropriate methodical support from the teaching staff in the organization of self-study of cadets both in the classroom and during extracurricular activities in a higher educational establishment. The importance of methodical content of self-study of cadets has to be limited to solving specific situations and problems using legal knowledge obtained from different disciplines. It is found out that the integration of educational content of cadets in the structure of methodical system of training including professional disciplines and practical preparation involves: the significance and importance of knowledge for cadets; understanding the material under study as a system; implementation of intra-subject and inter-subject relationships; legal orientation of professional courses and practical training. It is proved that all the factors of professional training of cadets in a higher educational establishment have complex positive impact on the formation of legal competence based on purposeful interaction of subjects in the educational process. Conclusions. The process of changing and development of higher education at present stage is characterized by increased emphasis on enhancing the role of self-study of cadets. The main purpose of self-study in a higher educational establishment is to improve the quality of professional training of cadets aimed at establishing the efficient system of basic and professional knowledge and skills that can be freely and independently applied in practice.